Observation Study on Distracted Driving Behaviour in Shah Alam Area - Makhtar, A.K.; Abdul Latib, M.H.; Md Isa, M.H. (Journal of the Society of Automotive Engineers Malaysia, 2021)
Distraction while driving among drivers is one of the factors which cause road accidents. Data from the Ministry of Transport Malaysia shows that accidents involving cars, vans, buses, lorries, 4-wheel drives and taxi drivers contribute to road accidents which involve 787,237 cases that is 82% from total cases in 2016. Distraction while driving is involving the lack of focus of a driver due to another task doing instead of driving. The distraction while driving includes mobile phone use, manipulating car navigation system devices or car’s features, eating or drinking, interaction with passengers and smoking. In Malaysia, there is not enough data regarding driver distraction. For example, research from the Malaysian Institute of Road Safety Research (MIROS) only depends on the survey regarding driver distraction while driving. The objective of this research is to determine the portion of drivers in Shah Alam who involve in the form of distracting activities while driving. The method for this research is a set of questionnaires to survey the distraction influenced by the age of the drivers. Next, a method of a real-life observation by using a high definition camera from upper view. The collected data is to investigate the differences between gender and between peak and non-peak hours for distracted driving. The observation took place in three selected locations which is the major road that consists of three lanes in Seksyen 7, Seksyen 19 and Seksyen 21. It is obtained that 9.5% of drivers observed in Shah Alam are distracted while driving. Next, the male is more into smoking compared with female. There is a slight difference between the other types of distraction. Next, as in total, peak hour shows that drivers tend to be distracted more than a non-peak hour. As for gender, younger drivers tend to be distracted by mobile phones compared with older drivers.